Fish polyculture as affected by culture season, stocking density and breed, under subtropical conditions of Egypt - MARAI, I F M; GABR, H A; AKAR, A M (The Indian Journal of Animal Sciences, 2014)
Effects of culture season, stocking density and breed, under Egyptian sub-tropical conditions, were studied on fish polyculture. The body weight, growth rate and fish yield were higher (P<0.01 and P<0.05) in summer than in winter crop, In Silver carp than In all other species and in 1.0 fish/cubic metre of water than in other stocking densities (fish yield). The feed conversion was hlgher (P<0.05) in winter than that in summer crop and in 3.0 fishes/cubic metre of water than in all other stocking densities. The condition factor was higher (P<0.05) in common carp than in all other species. The edible parts were higher (P<0.05) in 1.0 fish than in all other stocking densities and in grey mullet breed than in all other species. The non-edible parts were insignificantly higher in summer than in winter crop.